Trends in materials engineering for the manufacture of photovoltaic solar cells - Cucaita Hurtado, Oscar Giovanni; Cabeza Rojas, Iván Orlando (Ingeniería Solidaria, 2017)
Introduction: This review article was written during the second half of 2016 and the first of 2017 at the School of Environmental Engineering, Universidad Santo Tomás. Photovoltaic solar energy has acquired an important role in the global context due to the use of renewable sources and the reduction of environmental impacts, as well as for being an influential participant in meeting the current energy demand. However, it has limitations such as dependence on the availability of radiation and the use of silicon as a raw material for solar cells.Methodology: We prepared a state of the art of different databases searched, mostly Science Direct and Scopus, on the different alternative materials and current trends and their perspective of operation and implementation.Results: The solar cells that are using different materials are presented, among which the Cadmium Telluride (CdTe) solar cells stand out for their low cost and considerable efficiencies.Conclusion: Copper, indium, gallium, selenium/sulfur (cigs) cells are characterized mainly by their high adsorption coefficient; however, the great challenge to overcome is to implement them in an industrial environment. Organic solar cells are highly efficient and low-cost for their potential use in the Colombian context.
Keywords: organic cells; solar cells; efficiency; solar energy; photovoltaic materials